Pemanfaatan Tepung Tapioka dengan Dosis Berbeda Sebagai Sumber Karbon Pembentuk Bioflok pada Media Pemeliharaan Benih Ikan Patin (Pangasius sp.) - Novi Mayang Runa (Journal of Aquaculture and Fish Health, 2019)
Biofloc technology is one of alternative method that used to control water quality on culture media using heterotrophic bacteria with addition of organic matter. This research was held to determine the effect of tapioca flour addition as source of biofloc carbon in culture media on water quality, survival rate and growth of catfish fry. The research held on February to March 2015 in Laboratorium Budidaya Perairan, Aquaculture Department, Agriculture Faculty of Sriwijaya University. Used completely randomized design with four treatments and three replications were addition of tapioca flour with C/N ration 5, 10, and 15 as carbon source. The result showed that addition of flour as carbon source with C/N ratio of 15 was the best treatment with 88% survival rate, absolute length 3,20 cm and absolute weight 2,26 g.